Clinical predictors for the prognosis of myasthenia gravis - Lili Wang; Yun Zhang; Maolin He (BMC Neurology, 2017)
Abstract Background Clinical predictors for myasthenia gravis relapse and ocular myasthenia gravis secondary generalization during the first two years after disease onset remain incompletely identified. This study attempts to investigate the clinical predictors for the prognosis of Myasthenia Gravis. Methods Eighty three patients with myasthenia gravis were concluded in this study. Baseline characteristics were analyzed as predictors. Results Relapse of myasthenia gravis developed in 26 patients (34%). Generalization developed in 34 ocular myasthenia gravis patients (85%). Other autoimmune diseases were observed more commonly in relapsed myasthenia gravis (P = 0.012). Second generalization group contained more late onset patients (P = 0.021). Ocular myasthenia gravis patients with thymus hyperplasia progressed more rapidly than those with other thymus pathology (P = 0.027). Single onset symptom of ocular myasthenia gravis such as ptosis or diplopia predicted early progression than concurrence of ptosis and diplopia (P = 0.027). Treatment effect including glucocorticoid, pyridostigmine, thymectomy, IVIG, immunosuppressive drugs did not show significant difference between the relapsed and non-relapsed groups. The treatment outcome also showed no difference between the single OMG and second generalized groups. Conclusions Occurrence of associated autoimmune disease can serve as a potential predictor for myasthenia gravis relapse. Either ptosis or diplopia, as well as thymic hyperplasia can predict generalization in the first six months.